Peranan Koperasi Simpan Pinjam Kopdit Sube Huter Nita Dalam Mendukung Permodalan Usaha Mikro Kecil Dan Menengah Di Kecamatan Nita - Benediktus Ricky Moan; Wihelmina Mitan; Paulus Libu Lamawitak (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The aim of this study was to identify and explain the role of the Sube Huter Kopdit Savings and Loans Cooperative in supporting micro, small and medium enterprises in Nita District. This study uses a qualitative descriptive analysis approach. Qualitative data types. Sources of data used in this study are primary data and secondary data. Data collection techniques were carried out by means of observation, interviews and documentation. The number of informants in this study were 7 people consisting of 1 KSP Kopdit Sube Huter employee and 6 MSME actors. The results showed that KSP Kopdit Sube Huter has a role in supporting capital for micro, small and medium enterprises as a means of providing funds and financial facilitators, but KSP Kopdit Sube Huter has not carried out marketing as a marketing facilitator.